Ichthyosiform sarcoidosis: a mimic of leprosy?. (28th December 2018) - Kaushik, A.; Vinay, K.; Narang, T.; Saikia, U. N.; Modi, M.; Prakash, M.; Dogra, S.
Abstract : Click here for the corresponding questions to this CME article.